Tetra-ARMS PCR analysis of angiotensinogen AGT T174M (rs4762) genetic polymorphism in diabetic patients: a comprehensive study - Akash, Muhammad Sajid Hamid; Shahid, Momina; Suhail, Shaleem; Rehman, Kanwal; Nadeem, Ahmed; Mir, Tahir Maqbool (Frontiers in Endocrinology, 2023)
Background and Purpose: Hypertension (HTN) is a multifactorial chronic disease that poses a significant global health burden and is associated with increased mortality rates. It often coexists with other conditions, such as cardiovascular, liver, and renal diseases, and has a strong association with diabetes mellitus. Insulin resistance and endothelial dysfunction commonly occur in individuals with both HTN and type 2 diabetes mellitus (T2DM). Genetic factors, along with environmental and pathological factors, play a role in the development of HTN. Recent studies have revealed the influence of single nucleotide polymorphisms (SNPs) in various genes on HTN. In this study, we aimed to investigate the genetic polymorphism of angiotensinogen (AGT) T174M (rs4762) and its association with HTN in diabetic patients. Methods: A total of 300 participants were enrolled in this study and divided into three groups: control, hypertensive, and hypertensive diabetic. Blood samples were collected, and predetermined biochemical parameters were assessed. Genotyping of the AGT T174M (rs4762) gene was conducted using Tetra ARMS PCR with specific primers.The study findings revealed a significant association between AGT T174M (rs4762) genotype and HTN in diabetic patients within the Pakistani population. The C/T genotype of AGT T174M (rs4762) was found to be significant in both the hypertensive and hypertensive diabetic participants compared to the control group. This genotype was identified as a risk factor for developing HTN in both the hypertensive and hypertensive diabetic participants.This study demonstrates a significant association between AGT T174M (rs4762) genetic polymorphism and HTN in diabetic patients. The C/T genotype of AGT T174M (rs4762) may serve as a potential marker for identifying individuals at risk of developing HTN, specifically in the hypertensive and hypertensive diabetic populations.Further research is warranted to elucidate the underlying mechanisms and validate these findings in larger cohorts.